ANALISIS STRUKTUR DAN KINERJA INDUSTRI KONFEKSI DI KOTA PEKANBARU - Nuryunita, Nuryunita; Azwar, Harahap; Deny, Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine how the structure and performance of the confection industry in Pekanbaru city. The method used in this research is quantitative descriptive methods. The type of data used in this research are primary data and secondary data. Where the primary data itself is obtained directly from respondents through interviews, documentation and questionnaires. While the secondary data itself is obtained through government agencies such as the Department of Industry and Trade of Pekanbaru City. The analytical method used in this research is a strategy of analyzing structure and industrial performance with the help of Market Share (MS, Concentration Ratio (CR), Indeks Herfiendahl-Hirschman (IHH), and Price Cost Margin(PCM). The results of the study of market share obtained the highest MS of 6,79% and the lowest MS of 1,25%. Research on the Concentration Ratio of 4 companies (CR4) in the confection industry in Pekanbaru City amounted to 24,55%. Indeks HerfiendahlHirschman (IHH) calculation is 0,048599. The average PCM value is 32,282%.Keywords : analisys of structure and performance, Market Share (MS), Cocentration Ratio (CR), Indeks Herfiendahl-Hirschman (IHH), Price Cost Margin (PCM).